The Role of Social Workers in Restoring Social Functioning in Addiction Recovery at Yayasan Grapiks - Zahwa Haningtya Wahyudi; Nabila Shaira Khaerunnisa; Aisha Kayla Putri Trenggono; Isvi Nurul Anisa; Yani Achdiani; Sarah Nurul Fatimah (Balai Publikasi Indonesia, 2025)
This study discusses the vital role of social workers in assisting the recovery process of individuals with drug addiction (NAPZA) at Grapiks Foundation, a social rehabilitation institution in Bandung, Indonesia. Addiction to addictive substances not only affects physical and mental health but also disrupts a person’s social life. Therefore, recovery of addiction requires a holistic approach involving medical, psychological, social, and spiritual aspects. This research uses a qualitative approach through interviews to understand how social workers at Grapiks Foundation support clients in restoring their social functioning. The findings show that social workers act as companions, educators, facilitators, and connectors between clients and their social environment. They apply various methods such as counseling, motivational therapy, life skills training, and spiritual-religious approaches. The main challenges in this process include the risk of relapse and the clients’ low awareness of their condition. These are addressed through empathetic support, family involvement, and continuous education. This study highlights the crucial role of social workers in helping individuals reintegrate into society as productive members.